2003
DOI: 10.1002/eji.200323707
|View full text |Cite
|
Sign up to set email alerts
|

Dominant effector memory characteristics, capacity for dynamic adaptive expansion, and sex bias in the innate Vα24 NKT cell compartment

Abstract: V § 24 natural killer T (NKT) cells are innate immune cells that recognize self and nonself glycolipids presented by CD1d molecules, and play immunoregulatory roles in autoimmunity and tumor immunity. We have investigated the circulating V § 24 NKT cells in a large cohort of human subjects. CCR7 -CD45RO + effector memory cells dominated both CD4 + and CD4 -NKT subsets, while a minority displayed a central memory phenotype. CD4 -central memory NKT cells, however, were atypical in that they largely lacked CD62L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
77
8
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 44 publications
13
77
8
7
Order By: Relevance
“…If the last possibility is correct then the CD4 Ϫ NK T cell could be a late-stage-activated NK T cell. This model is supported by the effector-like phenotype of CD4 Ϫ NK T cells, with high levels of CD11a and CCR5 and loss of CD62L, and by the recent observation that human subjects with an expanded V␣24 NK T cell compartment have a preferential expansion of CD4 Ϫ NK T cells (28). If this model is correct, then CD4 could be viewed as a V␣24 NK T cell differentiation marker that is lost upon maturation into a late-stage effector-type cell.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…If the last possibility is correct then the CD4 Ϫ NK T cell could be a late-stage-activated NK T cell. This model is supported by the effector-like phenotype of CD4 Ϫ NK T cells, with high levels of CD11a and CCR5 and loss of CD62L, and by the recent observation that human subjects with an expanded V␣24 NK T cell compartment have a preferential expansion of CD4 Ϫ NK T cells (28). If this model is correct, then CD4 could be viewed as a V␣24 NK T cell differentiation marker that is lost upon maturation into a late-stage effector-type cell.…”
Section: Discussionmentioning
confidence: 87%
“…The balance between these two subsets is most probably important for the immunoregulatory role of the V␣24 NK T cell compartment. Another interesting feature of NK T cells is their uniform memory T cell-like phenotype with expression of CD45RO and CD28 and frequent expression of CCR5 (27,28). This phenotype may be linked to their role as innate immune cells, lending them the ability to respond rapidly to CD1d-restricted stimuli.…”
Section: H Uman Natural Killer (Nk) T Cells Are Innate Immune Cellsmentioning
confidence: 99%
“…Earlier studies suggested that NKT cell numbers may be influenced by age 22 or gender. 23 However, results from those studies were unclear since they also included a large population of non-NKT Va24 þ Vb11 À T cells. Nevertheless, recently we also observed a marginal, yet nonsignificant age-related reduction in circulating Va24 þ Vb11 þ NKT cells in healthy controls 28 and with an extended group of healthy elderly controls we now show that circulating NKT cell numbers significantly decrease with advancing age and that this decrease is more prominent in males than in females.…”
Section: Discussionmentioning
confidence: 99%
“…18 Thus far, data on the putative decrease of NKT cell numbers in cancer patients have been obtained from relatively small patient cohorts, 17,19,20 whereas actually normal Va24 þ Vb11 þ NKT cell numbers in cancer patients were reported in another study. 21 Importantly, the potential influence on circulating NKT cell numbers of both age, as described by DelaRose et al, 22 and gender, as described by Sandberg et al, 23 was not taken into account.…”
Section: Vb11mentioning
confidence: 99%
“…Cytokine expressions were detected by flow cytometry after stimulation with α‐GalCer in vitro as described 27. Isolated PBMCs (1 × 10 6 cells/well) were incubated in RPMI 1640 medium supplemented with 10% foetal bovine serum, in the presence of α‐GalCer (200 ng/mL; BioVision Incorporated, Milpitas Boulevard, Milpitas, USA) or 0.1% DMSO (as control) in a 12‐well plate at 37°C in a humidified incubator containing 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%